2021
DOI: 10.1155/2021/8858412
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Pulp‐Derived Mesenchymal Stem Cell Potential to Differentiate into Smooth Muscle‐Like Cells In Vitro

Abstract: Previous studies have shown that mesenchymal stem cells (MSCs) derived from various tissue sources can be differentiated into smooth muscle-like cells (SMLCs) in vitro. In this paper, dental pulp-derived mesenchymal stem cells (DPSCs) were evaluated for their differentiation ability towards smooth muscle-like cells (SMLCs) under the effect of widely used cytokines (TGF-β1 and PDGF-BB) with special focus on different culturing environments. For this purpose, both the commercially used culturing plates (Norm-c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Its potential differentiation ability plays an important role in the process of inflammation, repair, cell necrosis, and regeneration of dental pulp tissue [32]. Consistently with previous reports [33,34], DPSCs exhibited multi-directional differentiation ability (adipogenesis and osteogenesis) and have strong expression of stem cell surface markers (CD73, CD90, and CD105). Moreover, cultured cells were also measured by other hematopoietic markers (CD14, CD20, CD34, and CD45) to rule out the possibility that it contains hematopoietic stem cells.…”
Section: Discussionsupporting
confidence: 85%
“…Its potential differentiation ability plays an important role in the process of inflammation, repair, cell necrosis, and regeneration of dental pulp tissue [32]. Consistently with previous reports [33,34], DPSCs exhibited multi-directional differentiation ability (adipogenesis and osteogenesis) and have strong expression of stem cell surface markers (CD73, CD90, and CD105). Moreover, cultured cells were also measured by other hematopoietic markers (CD14, CD20, CD34, and CD45) to rule out the possibility that it contains hematopoietic stem cells.…”
Section: Discussionsupporting
confidence: 85%
“…Due to the potential versatility and easy accessibility, DMSCs are considered to be applicable as precursors for myogenic differentiation. Several studies have demonstrated that DPSCs possess the capacity of differentiating into smooth muscle cells (SMCs) in vitro under myogenic induction (Song et al, 2016;Jiang et al, 2019;Ha et al, 2021). Most of the studies focus on bladder SMCs as well as vascular SMCs (Song et al, 2016).…”
Section: Myogenesismentioning
confidence: 99%
“…Apart from this, the presence of DPSCs within the nerve was indicative of their involvement in transected nerve repair [ 39 ]. Several studies have highlighted the potential of DPSCs to differentiate into smooth muscle cells when provided with suitable myogenic induction [ 166 , 167 , 168 ].…”
Section: Oral Stem Cell-mediated Regeneration Of Other Tissuesmentioning
confidence: 99%